COMPLICATIONS OF NEOADYAVANT THERAPY FOR CANCER OF THE HEAD OF THE PANCREAS - R. I. Rasulov; M. V. Zemko; A. V. Shelekhov; K. G. Zubrinckiy; G. I. Songolov (Сибирский онкологический журнал)
Aim: to study complications of preoperative chemoembolization of the gastroduodenal artery and external beam radiation therapy in patients with pancreatic head cancer.Material and Methods. Sixty patients underwent chemoembolization of the gastroduodenal artery and external beam radiation therapy. Femoral artery angiography was performed using the Seldinger’s technique. Lipiodol 5–7 ml and gemcitabine 400 mg/m2 were used for transarterial chemoembolization. Radiation therapy was given at a total dose of 50 Gy (2 Gy/fraction, 5 times a week, over 5 weeks) using AGAT -R apparatus.Results. Complications after chemoembolization of the gastroduodenal artery were observed in 18.3 % of patients: abdominal pain in 3.3 % of patients; pain and nausea in 3.3 %; pain, nausea and fever in 6.7 %; pain, nausea and increased blood amylase in 1.7 %; pain, nausea and fever, blood amylase in 1.7 %; nausea, fever and blood amylase in 1.7 %. Radiation-induced injuries were observed in 23.3 % of patients: erythema in 18.3 %, grade 1 leukopenia in 1.7% and grade 2 leukopenia in 3.3 %.Conclusion. Complications of neoadjuvant therapy in terms of frequency and severity were consistent with literature data, were manageable with conservative treatment, and did not increase the duration of the preoperative period.